Ontology and sacrality – the two translative dominants of the works by Thomas Pynchon - Barciński, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article deals with the concept of dominant with regard to the translation process and various definitions of this term (e.g. the translative dominant as defined by Bednarczyk). Then the study presents the works by Thomas Pynchon, a leading postmodern American writer, stressing the possibility of applying a wide spectrum of translative dominants to his multifaceted fiction, which explores the aesthetic ambiguities within the postmodern literary convention. Finally, the article offers two main translative dominants as adequate for the analysis of Pynchon’s works in translation i.e. the ontological dominant and the sacral dominant. The description of the ontological dominant draws heavily on McHale’s understanding of this concept, while the discussion of the sacral dominant involves the possible analogy of approach to translation between texts within the postmodern convention such as Pynchon’s and sacral texts e.g. the Bible.
Keywords: dominant; postmodern literature; ontology; sacrality